PRODUCTION OF FE2O3 FROM FESO4.XH2O FORMED IN GALVANIZING WORKS - ARSLAN, M; ALKAN, C; CICI, M; KAYA, M (Elsevier Science Bv, 1994)
FeSO4.xH2O is generated in large amounts in galvanizing workshops. It can be reutilized by conversion to Fe2O3. In this study, the recovery of Fe2O3 from FeSO4.xH2O formed in the galvanizing process has been examined. The experimental work was carried out at various temperatures and times in the oxidizing medium. The reaction temperatures and times were selected as 450, 500, 550, 600, 650, 700, 800 and 900-degrees-C, and 15, 30, 45, 60,90 and 120 minutes, respectively. In order to determine the amount of Fe2O3, a titrimetric method was applied. The reaction products were characterized by means of IR and XRD techniques. The extent of conversion is low at temperatures below 650-degrees-C. Almost all of the iron(II) sulfate in the original sample was converted to iron(III) oxide at 650-degrees-C (120 min), 700-degrees-C (90 min), 800-degrees-C (60 min) and 900-degrees-C (45 min).